2017
DOI: 10.1097/inf.0000000000001551
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Identification of Group B Streptococcus and Escherichia Coli in Young Infants with Meningitis Using the Biofire Filmarray Meningitis/Encephalitis Panel

Abstract: FilmArray Meningitis/Encephalitis (ME) polymerase chain reaction (PCR) panel was tested on 62 cerebrospinal fluid (CSF) samples from young infants (0-3 months) with suspected meningitis and compared with CSF cultures. Twelve CSF samples from 9 infants were positive by ME PCR panel (10 Group B Streptococcus (GBS) and 2 Escherichia coli) of which only 5 were positive by culture. The 7 CSF samples that were positive only by ME PCR panel were obtained from infants who had received prior antibiotic treatment. The M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 11 publications
6
33
4
1
Order By: Relevance
“…Syndrome-based testing represents a paradigm shift in the diagnosis of infectious diseases, and our results, along with those of previously published studies, suggest that the use of multiplex molecular panels may assist in the diagnosis of CNS infections. Specifically, multiplex panels may play an important role when antimicrobials are administered empirically prior to collection of a CSF sample, thereby potentially impacting the sensitivity of culture-based methods (24,25). However, routine implementation of multiplex CNS panels, such as the FilmArray ME panel, will require careful consideration and thoughtful utilization management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Syndrome-based testing represents a paradigm shift in the diagnosis of infectious diseases, and our results, along with those of previously published studies, suggest that the use of multiplex molecular panels may assist in the diagnosis of CNS infections. Specifically, multiplex panels may play an important role when antimicrobials are administered empirically prior to collection of a CSF sample, thereby potentially impacting the sensitivity of culture-based methods (24,25). However, routine implementation of multiplex CNS panels, such as the FilmArray ME panel, will require careful consideration and thoughtful utilization management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, N. meningitides, a worldwide leading meningitis pathogen, and L. monocytogenes detected in none of the samples [6]. Meanwhile, clinical data on the performance of the FilmArray ME was reported by various users worldwide [7][8][9][10][11][12][13] with diagnostic specificity and sensitivity in good concordance to the multicenter study Admittedly, both false positive and false negative detections have been reported throughout the studies, with one example of an erroneously diagnosed HSV-1 meningitis in a patient with an underlying tuberculous meningitis [14] and one study indicating a potential of missing viral infections in a pediatric cohort [10]. Aside from the inarguably higher costs of multiplex molecular detection methods compared to standard laboratory procedures like bacterial culture, the remaining uncertainty in interpretation of results is a key point in the controversial discussion concerning the clinical utility of such syndromic testing approaches in infectious meningitis/ encephalitis [15].…”
Section: Introductionmentioning
confidence: 99%
“…This means that prior to the FilmArray ME panel, there were limited options available to clinicians desperate to identify a definitive etiology in the absence of a positive culture. Small numbers of studies and case reports have noted increased detection of bacterial targets by the FilmArray ME panel alone (8,(17)(18)(19)(20). A study of 62 CSF samples from young infants tested by the FilmArray ME panel reported 7 more positive results for bacterial targets than found with culture; 7 of the positive results were from infants that received antibiotics prior to lumbar puncture (18).…”
mentioning
confidence: 99%
“…Small numbers of studies and case reports have noted increased detection of bacterial targets by the FilmArray ME panel alone (8,(17)(18)(19)(20). A study of 62 CSF samples from young infants tested by the FilmArray ME panel reported 7 more positive results for bacterial targets than found with culture; 7 of the positive results were from infants that received antibiotics prior to lumbar puncture (18). Within the first 4 months of implementation, the FilmArray ME panel identified two cases of culture-negative bacterial meningitis (S. pneumoniae and L. monocytogenes) that were confirmed by positive blood cultures (14).…”
mentioning
confidence: 99%